Komparasi Sistem Pendidikan Jepang Dan Indonesia di Era Kontemporer - Niswah, Khoirun; Sassi, Komarudin (Faidatuna, 2023)
The education system in Indonesia tends to prioritize cognitive aspects, such as academic scores and exams, with less emphasis on affective and psychomotor aspects. This article examines the comparison between the education systems of Indonesia and Japan as developed countries that have advantages in this regard. Japan, with its superior education system, focuses on developing affective, cognitive and psychomotor aspects, as well as instilling normative values ​​from an early age. This comparative evaluation is the basis for advancing the Indonesian education system in a more holistic direction. Some of the findings include differences in educational philosophy, decentralization, educational goals, curriculum flexibility, funding, educational personnel qualifications, and examination approaches. The results of this evaluation can be a reference for improving and advancing the Indonesian education system so that it is able to create a golden generation in the future.